Psalm 69 : 23a-30b and divine retribution - a question of Ma'at? - Groenewald, Alphonso (Old Testament Essays, 2002)
The strophe comprising the cola 23a-30b is characterised by a remarkable series of imprecations which the supplicant directs against all those enemies who act against him in villainy (23a-29b). The supplicant appeals to God to let justice triumph by redressing the injustices he suffers on behalf of him (God). These imprecations should therefore impel God to make an end to the discrepancies existing between the enemies' deeds and their (apparent) well-being. Clearly the theme of divine retribution functions as the hermeneutical key in order to understand, not only this strophe, but also this Psalm. The question to be answered in this paper is what should one understand by the so-called 'doctrine of divine retribution' and what is the theology underlying this doctrine? In order to do this I will outline different views on the doctrine of divine retribution, as an underlying element of wisdom theology. This outline will especially focus on the opposing views held by K Koch and B Janowski on this issue. Whereas Koch emphasises the natural automatism inherent in the deed-consequence-nexus, Janowski follows in Assman's footsteps by defining retribution in ancient Israel in terms of 'connective justice' (iustitia connectiva); which could be explicated with the ancient Egyptian concept Ma'at, which represents the principle of solidarity, reciprocity and retribution. Having given this overview of the different viewpoints, this paper will defend the thesis that, in line with Janowski, Jan Assman's view of this doctrine can contribute to a better understanding of this series of imprecations included in the present BHS text of Psalm 69.
free